Friction losses in valves and fittings for power-law fluids - Polizelli, M.A. [UNESP]; Menegalli, F.C.; Telis, V.R.N. [UNESP]; Telis-Romero, J. [UNESP] (Brazilian Society of Chemical Engineering, 2003)
Data on pressure drop were obtained in stainless steel, sanitary fittings and valves during laminar and turbulent flow of aqueous solutions of sucrose and xanthan gum, which were selected as model fluids. The rheological properties of these solutions were determined and the power-law model provided the best fit for experimental data. Friction losses were measured in fully and partially open butterfly and plug valves, bends and unions. Values of loss coefficients (k f) were calculated and correlated as a function of the generalized Reynolds number by the two-k method. The model adjustment was satisfactory and was better in the laminar flow range (0.976 < r² < 0.999) than in the turbulent flow range (0.774 < r² < 0.989). In order to test the adequacy of the results for predicting loss coefficients during flow of real fluids, experiments were conducted with coffee extract. Comparison between experimental and predicted loss coefficients showed very good agreement.
Keywords: Pressure drop; non-Newtonian fluids; Friction factor; Loss coefficients